1989
DOI: 10.1109/26.24594
|View full text |Cite
|
Sign up to set email alerts
|

Delayed decision-feedback sequence estimation

Abstract: Delayed decision-feedback sequence estimation (DDFSE) is a detection algorithm that prpvides a direct tradeoff between complexity and performance in digital co~munications over intersymbol interference channels. The complexity of the algorithm is controlled by a pqrameter p and can be varied from zero tfl the lpemory of the channel (which can be infinite). The algorithq is based on a trellis with the number of states exponential in p. Whey p = Q, QDFSE requces to the decision-feedback detector. When the qemory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
234
0
4

Year Published

1992
1992
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 635 publications
(247 citation statements)
references
References 12 publications
0
234
0
4
Order By: Relevance
“…For channels with large delay spread, the optimum equalization algorithm, that is, the maximum likelihood sequence detector (MLSD) [1], is often too complex. For practical implementation, a suboptimum that allows a favorable trade off between complexity and performance is the delayed decision feedback sequence detector (DDFSD) [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For channels with large delay spread, the optimum equalization algorithm, that is, the maximum likelihood sequence detector (MLSD) [1], is often too complex. For practical implementation, a suboptimum that allows a favorable trade off between complexity and performance is the delayed decision feedback sequence detector (DDFSD) [2].…”
Section: Introductionmentioning
confidence: 99%
“…In [2] the noise whitening prefilter of [1] was considered before the DDFSD (W-DDFSD). In [3] has been shown that performance, especially for highly frequency selective channels, can be improved by adopting the mean-square prefilter (MS-DDFSD).…”
Section: Introductionmentioning
confidence: 99%
“…Two of the more well known techniques are reduced state sequence estimation [EQ88] and delayed decision feedback estimation [DHH89]. Tree-search algorithms can be partitioned into optimal and suboptimal approaches.…”
Section: Decision Feedback Equalizationmentioning
confidence: 99%
“…Duel-Hallen and Heegrad [17] developed the method of the delayed decisionfeedback sequence estimation (DDFSE) . Their main ideas are to define the states of trellis by considering the first few terms of ISI, and to include an estimate of the tail of ISI in the definition of branch metrics.…”
Section: Suboptimal Viterbi-like Algorithmsmentioning
confidence: 99%